Qualitative Analysis of the Literacy and Numeracy Habituation Program on the Critical Thinking Skills of Grade III Students at SDN Pendem 01 - Karisma Kamila; Innany Mukhlishina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Elementary education plays a vital role in developing students’ critical thinking skills, particularly through literacy and numeracy habits. This study aims to analyze the contribution of literacy and numeracy habits on the thinking skills of third-grade students at SDN Pendem 01. This study used a descriptive qualitative approach, with data collection techniques including interviews, observation, and documentation. Data were analyzed using source triangulation methods and techniques to achieve valid and comprehensive results. The results of the study indicate that literacy habits such as storytelling and chain Reading, and numeracy habits such as counting, quizzes, and puzzles, play an essential role in improving students’ critical thinking skills in the areas of interpretation, analysis, evaluation, and inference. Interviews with the principal, teachers, and students indicate that these habits not only improve numeracy skills but also foster self-confidence, independence, and reflective skills. Overall, literacy and numeracy habits at SDN Pendem 01 are proven effective in developing students’ critical thinking skills through fun contextual activities and a focus on meaningful learning. These findings suggest that the literacy and numeracy habituation program significantly contributes to the development of students’ critical thinking skills through contextual, interactive, and meaningful learning.